Efficiency and Productivity of Banking Sector in Nepal - K.C., Samprabha; Yadav, Reema; Karki, Resha; Mahato, Sandip Kumar; Paudel, Sangita; Neupane, Santoshi; Rawat, Ramesh (Nepalese Journal of Economics, 2025)
This study examines the efficiency and productivity of banking sector in Nepal. Efficiency and productivity are the selected dependent variables. The selected independent variables are capital, deposit, human resource cost, loan and advances, bank credit, and bank size. The study is based on secondary data of 10 commercial banks with 100 observations for the study period from 2014/15 to 2023/24. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of efficiency and productivity of banking sector in Nepal. The study showed that capital has a positive impact on efficiency and productivity. It indicates that increase in capital leads to increase in efficiency and productivity. Similarly, deposit has a positive impact on efficiency and productivity. It indicates that increase in deposit leads to increase in efficiency and productivity. Likewise, human resource cost has a positive impact on efficiency and productivity. It indicates that increase in expenses on human resource leads to increase in efficiency and productivity. Further, loan and advance have positive impact on efficiency and productivity. It indicates that higher the loan and advances, higher would be the efficiency and productivity. In addition, bank size has a positive impact on efficiency and productivity. It indicates that larger the bank size, higher would be the efficiency and productivity.